L’avènement de l’art naïf en Haïti. La portée instauratrice d’un jugement esthétique - Célius, Carlo (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2004)
A number of scholars have sought to explain the emergence of naïve art in Haiti. They have put forth a range of factors: historical, sociological, and anthropological. A brief analysis of the main arguments advanced reveals that these explanatory models are far from satisfactory. The argument defended here is that the naïve art movement in Haiti began when an outside curator assigned aesthetic value to the work of a naïve painter. This aesthetic judgement created a conceptual foundation upon which the new movement would be based, initiating a process of institutionalization and collective organization, and giving the painters a new sense of identity.